Effect of inhalational salbutamol ipratropium combination versus salbutamol in asthmatic children: A meta-analysis - Preethi Tamilarasan; Reenaa Mohan; Jenifer Florence Mary J; Shalini Balamurugan; Kalaiselvan G (Journal of Krishna Institute of Medical Sciences University)
Background: Ipratropium, an inhaled short-acting anticholinergic, has a delayed beginning of action than salbutamol, but it has been established as an alternative and add-on to short-acting beta-agonist for adults. The combination was also shown to have less negative effects. Aim and Objectives: The study's goal was to compare the efficacy of salbutamol ipratropium combination to salbutamol alone in asthmatic children, taking into account studies completed within the preceding five years to acquire the most recent data. Material and Methods: The meta-analysis contains all published trials evaluating the efficacy of salbutamol ipratropium combined with salbutamol alone in asthmatic children. A pre-set checklist was used to help with data extraction. A complete and systematic review of research published up until 2024 was undertaken using a combination of Medical Subject Headings (MeSH), and free-text keywords from sites such as Google Scholar and PubMed. The data was examined using Review Manager (version 5.4). A random effect model was used to compare the impact of salbutamol + ipratropium to salbutamol alone. The primary aim was to measure improvement in Peak Expiratory Flow Rate (PEFR) as a mean (SD), with clinical scores in asthmatic children serving as the secondary outcome (Prospero Registration: CRD42024514294). Results: A total of 291 patients were assigned to the intervention and control groups, respectively. The average age of the cohorts included in this study varied from 4.52 to 9.92 years. Salbutamol was coupled with ipratropium bromide in the intervention group, whereas salbutamol was administered alone in the control group. The trials spanned six to twenty-four months. Salbutamol and ipratropium substantially improved PEFR during bronchial asthma treatment (MD = 17.90, 95% CI 213.42-22.39, p < 0.001). A substantial Q statistic (p < 0.001) indicated heterogeneity (I = 86%). Combining salbutamol and ipratropium led to a reduced clinical score for bronchial asthma (MD = 0.57, 95% CI 1.37 - 0.22, p < 0.14) (Figure 23). The negligible Q statistic (p < 0.16) indicated heterogeneity (I = 55%). Conclusion: In our country, the combination of salbutamol and ipratropium can be used as the first line therapy for asthma attacks, lowering hospitalizations and episode intensity, benefiting both patients and the healthcare system.